Genetic resiliency and the Black Death: No apparent loss of mitogenomic diversity due to the Black Death in medieval London and Denmark. Issue 2 (9th April 2019) - Klunk, Jennifer; Duggan, Ana T.; Redfern, Rebecca; Gamble, Julia; Boldsen, Jesper L.; Golding, G. Brian; Walter, Brittany S.; Eaton, Katherine; Stangroom, Julianna; Rouillard, Jean‐Marie; Devault, Alison; DeWitte, Sharon N.; et al.
Abstract: Objectives: In the 14th century AD, medieval Europe was severely affected by the Great European Famine as well as repeated bouts of disease, including the Black Death, causing major demographic shifts. This high volatility led to increased mobility and migration due to new labor and economic opportunities, as evidenced by documentary and stable isotope data. This study uses ancient DNA (aDNA) isolated from skeletal remains to examine whether evidence for large‐scale population movement can be gleaned from the complete mitochondrial genomes of 264 medieval individuals from England (London) and Denmark. Materials and Methods: Using a novel library‐conserving approach to targeted capture, we recovered 264 full mitochondrial genomes from the petrous portion of the temporal bones and teeth and compared genetic diversity across the medieval period within and between English (London) and Danish populations and with contemporary populations through population pairwise ΦST analysis. Results: We find no evidence of significant differences in genetic diversity spatially or temporally in our dataset, yet there is a high degree of haplotype diversity in our medieval samples with little exact sequence sharing. Discussion: The mitochondrial genomes of both medieval Londoners and medieval Danes suggest high mitochondrial diversity before, during and after the Black Death. While our mitochondrial genomic data lack geographically correlated signals, these data could be the result of high, continual female migration before and after the Black Death or may simply indicate a large female effective population size unaffected by the upheaval of the medieval period. Either scenario suggests a genetic resiliency in areas of northwestern medieval Europe.